Depletion of WFS1 compromises mitochondrial function in hiPSC-derived neuronal models of Wolfram syndrome - Zatyka, Malgorzata; Rosenstock, Tatiana R.; Sun, Congxin; Palhegyi, Adina M.; Hughes, Georgina W.; Lara-Reyna, Samuel; Astuti, Dewi; di Maio, Alessandro; Sciauvaud, Axel; Korsgen, Miriam E.; Stanulovic, Vesna; Kocak, Gamze; et al. (Stem cell reports, 2023)
Mitochondrial dysfunction involving mitochondria-associated ER membrane (MAM) dysregulation is implicated in the pathogenesis of late-onset neurodegenerative diseases, but understanding is limited for rare early-onset conditions. Loss of the MAM-resident protein WFS1 causes Wolfram syndrome (WS), a rare early-onset neurodegenerative disease that has been linked to mitochondrial abnormalities. Here we demonstrate mitochondrial dysfunction in human induced pluripotent stem cell-derived neuronal cells of WS patients. VDAC1 is identified to interact with WFS1, whereas loss of this interaction in WS cells could compromise mitochondrial function. Restoring WFS1 levels in WS cells reinstates WFS1-VDAC1 interaction, which correlates with an increase in MAMs and mitochondrial network that could positively affect mitochondrial function. Genetic rescue by WFS1 overexpression or pharmacological agents modulating mitochondrial function improves the viability and bioenergetics of WS neurons. Our data implicate a role of WFS1 in regulating mitochondrial functionality and highlight a therapeutic intervention for WS and related rare diseases with mitochondrial defects. [Display omitted] •Wolfram syndrome patient-derived neuronal cells exhibit mitochondrial dysfunction•Loss of WFS1 interaction with VDAC1 could potentially affect mitochondrial function•Mitochondrial and cell death phenotypes are rescued by genetic correction•Pharmacological agents rescue mitochondrial defects and improve neuronal viability In this article, Sarkar and colleagues describe mitochondrial dysfunction in neuronal cells generated from patient-derived iPSCs of Wolfram syndrome, a rare early-onset neurodegenerative disorder. Genetic rescue by WFS1 restoration or chemical rescue by drugs modulating mitochondrial function improves the bioenergetics and viability of Wolfram syndrome patient neurons, thus providing insights for therapeutic intervention.